Leprosy in Sukkur region: A series of 143 cases from 2001-2011 at leprosy centre Sukkur, Sindh - Shaikh, Irfan; Soomro, Farooq; Bhatti, Nuzhat Seema; Bhutto, Abdul Manan (Journal of Pakistan Association of Dermatologists, 2016)
Objective To document the clinical characteristics of newly diagnosed leprosy patients in Sukkur Region, Sindh. Â Methods A total of 143 new leprosy cases referred and registered in leprosy centre, Sukkur from 2001-2011 were studied. Diagnosis was based on clinical grounds, and supported by acid-fast bacilli on slit-skin smear. Â Results Out of 143 new cases 73 (51%) were males and 70 (49%) females. The peak age of disease onset was second decade. The most common form of the disease was borderline tuberculoid (BT) seen in 76 (53%) cases. Ulnar nerve was the most frequently affected nerve seen in 30 (21%) cases. Â Conclusion Although in urban cities the cases of leprosy are in decline but still it exists in rural areas of Sindh. It is important for the practitioners to be aware of its diagnosis and management to prevent the deformities Â